Distal aiming device versus free hand technique for distal locking screw insertion time in femoral nail: A prospective cohort study - Niramitsantiphong, Anugoon; Kongrit , Athipong; Sornsa-ard , Tuanrit; Jinlawal , Bunyarit (Journal of Nakornping Hospital, 2025)
Background: Distal locking screw placement is a challenging procedure for intramedullary nail of femoral shaft fracture. Assisting by aiming device may decrease operative time and reduce radiation exposure time compared to free hand technique. Objectives: To compare the operative time for locking distal screw, fluoroscopic time and numbers of fluoroscopic shot for locking distal screw in two different techniques which were aiming device and free hand techniques. Research Methodology: A prospective cohort study conducted in patients with femoral shaft fractures were treated using intramedullary nails, with two different techniques for distal locking screw insertion: the freehand technique and the aiming device technique. This study was conducted between July 1, 2020, and April 1, 2022, at Nakornping Hospital in Chiang Mai, Thailand. The primary outcome measured was the distal screw insertion time. Secondary outcomes included fluoroscopic time and the number of fluoroscopic shots during distal screw insertion. According to data analyses, intention-to-treat strategies were applied. T-tests, the rank-sum test, and Fisher's exact probability test were performed to compare the differences. Results: Thirty patients underwent the aiming device technique, while 28 patients received the freehand technique. Although there was no significant difference in distal screw insertion time between the two methods, the aiming device technique significantly reduced fluoroscopic time, with median values of 19 seconds (range: 24.3-224 seconds) compared to 52.5 seconds (range: 35.5-103 seconds), p-value < 0.001. In the aiming device group, eight patients (26.67%) were switched to the freehand technique, primarily due to infra-isthmal femoral fractures, with a conversion rate of 62.5% in these cases (p-value < 0.05). Conclusion: The study found no statistically significant difference in screw insertion time between the group using an aiming device and the group using freehand technique. However, the group using the aiming device required significantly less fluoroscopic assistance during surgery. Nonetheless, there was a higher likelihood of switching to the freehand technique, particularly in cases of infra-isthmal femoral fractures. Thai Clinical Trial Registry: TCTR20230221005